Perancangan Sistem Pakar Untuk Mendiagnosa Penyakit Nyeri Perut Dengan Metode Teorema Bayes Berbasis Web - Ningsih, Sri Purnama; Candra, Feri; Zulharman, Zulharman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
People who still do not pay attention to a stomachache disorder, due to the busyness of their daily activities. With this, many people experience stomach pain at an already serious stage and even difficult to treat. Due to lack of attention to early symptoms. With this we need someone who is an expert in their field, namely an expert. So that the problems that occur can be resolved properly according to the correct handling procedure. Expert systems can help deal with problems that require expertise in certain fields. One of them is in the health sector, especially in handling abdominal pain. This expert system is very helpful in making decisions, from this expert system can collect and store knowledge by someone or several people from experts in a knowledge base and use a reasoning system resembling an expert in solving problems. This research will use the Bayes theorem method because it fits very well with the existing problems. To test the accuracy of the testing data obtained by experts with expert system output, the appropriate output results are obtained with an accuracy rate of 94.44%.Keywords: Stomach Pain Diseases, Expert System, Bayes Theorema